PENERAPAN EXTREME PROGRAMMING PADA PEMBUATAN APLIKASI BUKU TAMU ADAPTIF DI KANTOR KOMISI PEMILIHAN UMUM KOTA PALANGKA RAYA - Erfan, Muhammad; Kurniawan, Tri Yohanes; Ashari, Muhammad Halim; Veronika, Yoshe Marwanda; Ofsiani, Rini; Wulandari, Desta; Tare, Kristian Lai (LPPM Universitas Bina Bangsa, 2023)
The Guest Book Information System Application (SIBTa) is a technological solution introduced for the General Election Commission (KPU) of Palangkaraya City to optimize data management, increase administrative efficiency, and improve services to the community. This research describes the development, implementation and impact of the digital guestbook application at the Palangkaraya City KPU. This application is designed to replace the physical guestbook that was previously used, with the aim of reducing paper usage, saving time, and increasing data security. This research includes the design, testing and application implementation stages. The result is a system that can be easily used by visitors who come to the Palangkaraya City KPU office